2013
DOI: 10.1186/cc12680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, sepsis interventions and outcomes in the obese patients with septic shock: an international multicenter cohort study

Abstract: IntroductionData are sparse as to whether obesity influences the risk of death in critically ill patients with septic shock. We sought to examine the possible impact of obesity, as assessed by body mass index (BMI), on hospital mortality in septic shock patients.MethodsWe performed a nested cohort study within a retrospective database of patients with septic shock conducted in 28 medical centers in Canada, United States and Saudi Arabia between 1996 and 2008. Patients were classified according to the World Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
188
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(209 citation statements)
references
References 38 publications
14
188
4
3
Order By: Relevance
“…However, in the context of critically ill oncologic patients with high BMI, the impact on mortality is unknown. Different reports have described that in patients with sepsis and septic shock, obesity is a protective factor against death (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of critically ill oncologic patients with high BMI, the impact on mortality is unknown. Different reports have described that in patients with sepsis and septic shock, obesity is a protective factor against death (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [16][17][18][19] have indicated that the outcomes (ie, hospital mortality) and characteristics (ie, type of underlying infection) of critically ill obese patients differ from those of nonobese patients. These differences may be due to underlying pathophysiological mechanisms or differential use of therapies or suboptimal drug dosing.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, 26% of adults worldwide were obese [1]. The proportion of extremely obese patients (BMI N 40 kg/m 2 ) in intensive care units varies between 2.8% and 6.8% [2][3][4][5][6][7]. A BMI higher than 40 kg/m 2 seems to be associated with an increased risk of developing acute respiratory distress syndrome (ARDS) along with greater morbidity, length of stay, and duration of mechanical ventilation in the intensive care unit (ICU) [8].…”
Section: Obesity (Body Mass Index [Bmi]mentioning
confidence: 99%